Legal Protection of Notaries Against Acts Against the Law on False Testimony by Presenters - Laurel Rahardjo; Mella Ismelina FR (Dinasti Research, 2025)
This study aims to determine the form of legal protection for notaries against unlawful acts of false statements by the parties and to determine the judge's considerations in determining the notary's responsibility for unlawful acts of false statements by the parties. The research method used is normative legal research. The results of the study indicate that the form of legal protection for notaries against unlawful acts of false statements by the parties is regulated in the Notary Law (UUJN). Article 66A of the UUJN stipulates that the summons of a notary for legal proceedings must obtain the approval of the Notary Honorary Council (MKN). The notary's responsibility is limited only to the formality of making a deed, while the material truth of the statement is the responsibility of the party appearing, as regulated in Article 16 paragraph (1) letter c of the UUJN. This protection is in accordance with the principle of the presumption of innocence and the position of a notary as a public official, and can be strengthened through legal steps if criminalization occurs. In the Supreme Court Decision Number 98 K/Pid/2021, the judge decided that the notary was not criminally responsible for false statements given by the party appearing in an authentic deed. This decision is based on the principle that the notary's responsibility is limited to the formal truth of the deed, while the material truth of the contents of the statement is entirely the responsibility of the person appearing.